L-Band amplitude scintillations during solar maximum at a low latitude station - Abdul Rahim, Nurliyana; Mokhtar, Mohd Hezri; Mat Nayan, Nadirul Hasraf; Ismail, Muhammad Yusof; M. Buhari, Suhaila; Abdullah, Mardina; Bahari, Siti Aminah (WARSE, 2020)
The Global Positioning System (GPS) is one of the most important and useful technologies developed for information and communication technology. Propagated wireless signals along the GPS link are affected by the ionospheric irregularities, therefore the GPS signals may experience ionospheric scintillation. In this study, GPS L-band amplitude scintillations observed at a low latitude station. Data from the Global Navigation Satellite System (GNSS) Ionospheric Scintillation and Total Electron Content (TEC) monitor (GISTM) receiver installed at the Space Science Centre (ANGKASA), Institute of Climate Change, UniversitiKebangsaan Malaysia, UKM (2.92°N, 101.78°E) were used for this study. Of the 460 scintillation (by neglecting S4<0.15) events recorded during February 2014, 55% were weak (0.15≤S4<0.25), 32% were moderate (0.25≤S4<0.35) and 13% were strong (S4≥0.35). For February 2014, the amplitude scintillations were most pronounced in the post-sunset time to pre-midnight time. Finally, these analysed data are used to study the variability of scintillation with solar activities.